2001
DOI: 10.1038/ng789
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 lysine 9 methylation is an epigenetic imprint of facultative heterochromatin

Abstract: Post-translational modifications of histone amino termini are an important regulatory mechanism that induce transitions in chromatin structure, thereby contributing to epigenetic gene control and the assembly of specialized chromosomal subdomains. Methylation of histone H3 at lysine 9 (H3-Lys9) by site-specific histone methyltransferases (Suv39h HMTases) marks constitutive heterochromatin. Here, we show that H3-Lys9 methylation also occurs in facultative heterochromatin of the inactive X chromosome (Xi) in fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
316
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(335 citation statements)
references
References 30 publications
12
316
0
7
Order By: Relevance
“…In contrast, methylation of lysine 9 of H3 is a marker of condensed, inactive chromatin of the sort associated with the inactive X-chromosome and pericentromeric heterochromatin. [48][49][50][51] There is a report that cancer cells have increased overall levels of deacetylation of the known histone target of SIRT1, H4-K16. 52 Moreover, a recent study also suggested that global histone modification in prostate cancer, including acetylation of H3K18 and H4K12, dimethylation of H3K4 and H4R3 and acetylation of H3K9, a target of SIRT1, 53 predict a risk of prostate cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, methylation of lysine 9 of H3 is a marker of condensed, inactive chromatin of the sort associated with the inactive X-chromosome and pericentromeric heterochromatin. [48][49][50][51] There is a report that cancer cells have increased overall levels of deacetylation of the known histone target of SIRT1, H4-K16. 52 Moreover, a recent study also suggested that global histone modification in prostate cancer, including acetylation of H3K18 and H4K12, dimethylation of H3K4 and H4R3 and acetylation of H3K9, a target of SIRT1, 53 predict a risk of prostate cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that methylation of histone, particularly of H3, is important to mark the inactive X; namely, H3 methylation provides an epigenetic imprint or a nucleation center for Xist RNA on the inactive X . Furthermore, the inactive X chromosome is enriched for H3 methylated at lysine 9 (H3-K9) (Boggs et al, 2002;Peters et al, 2002). It has also been demonstrated that histone methylation occurs prior to DNA methylation of CpG island (Brockdorff, 2002).…”
Section: Dna Methylation In Various Biological Phenomenamentioning
confidence: 98%
“…Despite anti-H3K27me3 antibodies also recognizing H3K27me2, and anti-H3K27me2 antibodies recognizing H3K27me3, both have a clear preference for their main substrates (Peters et al, 2002). Thus, the main methylation mark on the PHE1 locus is H3K27me3.…”
Section: The Pheres1 Locus Contains H3k27 Methylation Marksmentioning
confidence: 99%